The "efficiency defense" in the US American merger policy - Konstanze Kinne (Hamburg Institute of International Economics (HWWA), 1998)
Efficiencies have yet not played a prominent role in American merger enforcement policy, although the federal antitrust agencies and the courts have recognized efficiencies as a factor in merger analysis that may tilt the balance in an otherwise anticompetitive transaction. A review of the development of the Merger Guidelines and an analysis of the case law reveals that the evaluation of efficiencies claims has evolved dramatically over the last few decades and that the trend has been toward a more sympathetic treatment of efficiencies claims. To date, however, no court has upheld an otherwise anticompetitive merger on the basis of efficiencies. The “second order importance“ of the efficiency argument in merger analysis is based on varied grounds. One reason for the limited significance of the efficiency defense in antitrust enforcement is, certainly, the scarcity of cases in which both substantial efficiencies and substantial market power coincide. In spite of that fact, efficiencies can, nevertheless, play a significant role in non-litigated merger cases. But as those cases never become public and the agencies do not disclose their reasons for allowing a merger, it is difficult to give a proper judgment of efficiencies in merger practice. Moreover, the courts' merger decisions have not contributed to shedding more light on that topic. Since the Supreme Court has not, since the Warren court era, addressed questions of relative weight and priority in the efficiency area, and the treatment of efficiencies in lower courts depends heavily on the outlook of a particular court, many issues are ambiguous and unsettled. Another reason for this infrequent application is the inherent nature of efficiencies. Since it is difficult to measure efficiencies, in particular ex ante, it is therefore troublesome to determine the magnitude of anticompetitive loss against which efficiency gains should be balanced. The problem of proof is the principal reason why the agencies and the courts have been quite skeptical of efficiencies claims. Instead of making the formal tradeoff, the analysis of the litigated merger cases indicates that judges tend to resolve that issue indirectly. In some cases, it appears that the courts compare the efficiencies losses of a less restrictive alternative to the proposed transaction with the anticompetitive harm resulting from the merger. In doing so, the courts get an idea of the relative weight of the efficiencies but avoid a direct balancing of benefits against costs. Finally, the strategic value of the efficiency defense has to be taken into account in order to understand the relatively small importance of efficiencies in antitrust policy. Antitrust agencies, which seek to block an anticompetitive merger in litigation, tend to place less weight on the efficiency argument because they want success in the lawsuit. Defendants, on the other hand, have an incentive to overestimate their efficiencies claims in order to win the case. The courts have, then, the difficult task of weighing the credibility of both sides' argumentation. It seems that courts tend to reject efficiencies claims when they find a proposed merger to be anticompetitive and to recognize efficiencies when the adverse competitive effects appear to be small.
Keywords: 330; Konzentrationspolitik; Fusionskontrolle; Fusion; Wirtschaftliche Effizienz; Vereinigte Staaten